The Influence Of Product Quality And Service Quality On Purchasing Interest Through Consumer Trust In The Bukalapak Application - ardhiana, nova arya; Sijabat, Rauly; P, Ratih Hesty Utami (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research aims to determine and analyze product quality and service quality on purchasing interest through consumer trust in the Bukalapak application (case study of the use of the Bukalapak application in the city of Semarang). The data used is through primary data by distributing questionnaires in Semarang with a sample of 400 respondents. This research uses quantitative methods. The results of this research show that product quality on consumer trust is 0.000 (positive and significant influence), product quality variable on purchase interest is 0.000 (positive and significant influence), service quality variable on consumer trust is 0.000 (positive and significant influence), quality variable Service on Purchase Interest is 0.000 (Positive and Significant Influence), Consumer Trust Variable on Purchase Interest is 0.000 (Positive and Significant Influence), Product Quality Variable on Purchase Interest Through Consumer Trust is 0.003 (Positive and Significant Influence), Service Quality Variable on Purchase Interest Through Consumer Trust of 0.001 (Positive and Significant Influence)